Combined Risk Factors and Digestive Disorders in Mid-Lactation Holstein Cows: A Case Study - S. T. Quanz; L. K. Mamedova; M. J. Brouk; P. Gott; B. J. Bradford (Kansas Agricultural Experiment Station Research Reports, 2019)
Digestive disorders can be a significant cause of disease on dairies and are frustrating because of their unpredictability. Diets that may support excellent health in most cases may nonetheless result in significant gastrointestinal disease, even leading to deadly conditions such as hemorrhagic bowel syndrome. To our knowledge, there is limited research on these conditions, as many risk factors fail to reproduce disease when experimentally administered to cows, leading many to conclude that these disorders are generally multifactorial in nature and difficult to replicate. In this case study, we document the outbreak and resolution of digestive disorders among 15 control cows enrolled in a larger production study. Over 14 weeks, cows were individually fed, with milk yield and composition, blood variables, and health observations recorded. The diet included drought-stressed corn silage that introduced difficulties including low energy density, high dry matter content (making it unstable at feedout), and mycotoxin contamination. By weeks 4–5 on the study, sporadic diarrhea began to appear and milk fat content had dropped from 3.7% to 3.4%, on average. Coincident with the onset of environmental heat stress, three cows developed severe digestive disorders, resulting in a displaced abomasum in one cow. At that point, the diet was changed to replace some corn silage with wheat straw, a direct-fed microbial was added to the diet, and organic acid treatment of the silage face was initiated. Within a month after these changes were implemented, essentially all signs of digestive problems resolved, including milk fat content, fecal consistency, and blood plasma concentrations of haptoglobin and D-lactate. This case study points to multiple factors that likely combined to lead to microbial and gastrointestinal disruptions resulting in clinical disease in a subset of cows.
Keywords: gut health; mycotoxins; heat stress; fiber